High-altitude Tibetan fermented milk ameliorated cognitive dysfunction by modified gut microbiota in Alzheimer's disease transgenic mice. Issue 6 (27th May 2020) - Liu, JunLi; Yu, ChunYang; Li, RunLe; Liu, KunMei; Jin, GuoEn; Ge, RiLi; Tang, Feng; Cui, Sen
Abstract : Heatmap of species composition in different yogurt samples (At genus level). Abstract : Alzheimer's disease (AD) is a complex neurodegenerative disease that is regarded as a growing global challenge. Accumulating evidence linking gut microbiota with AD has become intriguing. The purpose of this study was to investigate how Tibetan fermented milk affected memory impairment in amyloid precursor protein (APP)/presenilin-1 (PS1) mice, using APP/PS1 transgenic mice as examples. We used Tibetan fermented milk (the yogurt samples with the highest microbial diversity were selected by 16S sequencing) as an intervention in such mice for 20 weeks, with aseptic maintenance feed as their basic diet. At the end of the intervention, we collected fecal samples for 16S ribosomal ribonucleic acid (rRNA) sequencing. We evaluated the effects of Tibetan fermented milk on the mice's cognitive function by behavioral examination, and deposition of amyloid beta (Aβ) in the hippocampus and cortex of the mice by immunohistochemistry (IHC). Results showed that Tibetan fermented milk could improve cognitive impairment in APP/PS1 mice, including spatial learning/memory and object recognition/memory. Sequencing of 16S ribosomal RNA in mouse feces showed that Tibetan fermented milk increased intestinal microbial diversity and elevated the relative abundance of Bacteroides and Faecalibacterium spp. Mucispirillum and Ruminiclostridium were highly abundant in APP/PS1 mice. Additionally, correlation analysis revealed that cognitive function was correlated negatively with Mucispirillum abundance and positively with Muribaculum and Erysipelatoclostridium abundance. Tibetan fermented milk could also reduce deposition of Aβ in the cerebral cortex and hippocampus. Our data suggested that long-term intake of Tibetan fermented milk had a beneficial effect on the composition of intestinal flora, which was correlated with cognitive improvements in APP/PS1 mice and seemed to help prevent and treat AD-induced cognitive decline.